Peran Pendidikan Dalam Mendorong Pertumbuhan Ekonomi: Studi Kasus Pada Program Studi Magister Manajemen Pendidikan Universitas Ahmad Dahlan - Noryani; Ami Aulia; Lailan Sawiah Siagian; Nurlaelah; Siti Halimah; Widyatmike Gede Mulawarman (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Education is a fundamental pillar in the development of quality human resources, which in turn drives a country’s economic growth. Universitas Ahmad Dahlan, as one of Indonesia’s leading educational institutions, is strongly committed to continually improving the quality of education through effective and efficient management. The PPL Internship Activity Report provides insights into education and economic growth within the Master of Educational Management Program at Universitas Ahmad Dahlan, Yogyakarta. The PPL activities are structured around planning, organizing, implementing, and monitoring stages. Data collection methods included interviews, observations, and documentation. The collected data was analyzed interactively through data reduction, data presentation, and conclusion drawing.The findings from the PPL activities revealed that (1) planning involved identifying human resource needs, formulating vision and mission statements, and developing a competency-based curriculum; (2) organizing included forming a team of professional lecturers, establishing partnerships with industry and government institutions, and providing supporting facilities; (3) implementation involved innovative teaching methods and the development of students’ soft and hard skills; and (4) supervision included student performance evaluations as well as curriculum review and enhancement. Overall, the planning, organizing, implementation, and supervision conducted by the Master of Educational Management Program at Universitas Ahmad Dahlan aim to develop high-quality human resources capable of contributing to economic growth. By strengthening managerial competencies, graduates are expected to become innovative leaders in the education sector, equipped to face global challenges and drive productivity and economic competitiveness at both the national and international levels.